Trisomy 20p/monosomy 18p associated with congenital bilateral perisylvian syndrome. Issue 3 (19th July 2022) - Bonardi, Claudia M.; Bayat, Allan; Madsen, Camilla G⊘bel; Hammer, Trine B.; Reale, Chiara; Gardella, Elena; Marjanovic, Dragan; Beniczky, Sandor; M⊘ller, Rikke S.; Rubboli, Guido
Abstract: We report the association, not previously described, between trisomy 20/ monosomy 18 and congenital bilateral perisylvian syndrome (CBPS), a condition featuring intellectual disability, epilepsy, oro‐motor dysfunction and bilateral perisylvian polymicrogyria (BPP) in a 29‐year‐old individual. Detailed clinical evaluation, long‐term EEG and EEG analysis by means of electrical source imaging (ESI), 3T MRI and array‐CGH were performed. Clinical examination showed moderate/severe intellectual disability, dysmorphic features, oro‐motor dysfunction, short stature, abnormal hands and feet, bradykinesia and abnormal posture. The patient had suffered from drug‐resistant epilepsy since infancy. Brain MRI showed that BPP was consistent with CBPS. Additional imaging features revealed corpus callosum and cerebellar hypoplasia and fusion of the C1‐C2 vertebrae. Ictal EEG and ESI documented tonic seizures originating from the right polymicrogyric cortex. Facial gestalt included dysmorphic features reported in patients with 18‐ and 20+ chromosomal rearrangements. Array‐CGH showed an unbalanced translocation, arr(18p)x1(20p)x3. In conclusion, we provide a detailed electro‐clinical and MRI description of a novel condition characterized by the association between trisomy 20p/monosomy 18p and CBPS, also illustrating its clinical evolution into adulthood. This information may help paediatricians, neurologists and geneticists to better counsel families about the developmental prognosis of this rare unbalanced chromosomal rearrangement.